Organizational climate and oil companies. Multidimensional study with workers from the drilling department in Tabasco, Mexico - González López, Carlos de Jesús; Sandoval Caraveo, María del Carmen; Surdez Pérez, Edith Georgina (Archives of Business Research, 2016)
The organizational climate is the perception of workers in a company about the processes of the organization and the relationships among its members. The aim of this study was to conduct a study of organizational climate to employees working in an oil company located in Tabasco, Mexico. The research is descriptive and correlational. The design is non-experimental with a quantitative approach. A questionnaire with a Likert scale and reliability of 0.838 in the Cronbach Alpha coefficient was used. The dimensions of organizational climate were autonomy, cohesion, support, work pressure and innovation. The ANOVA analysis of variance reported a statistically significant difference between cohesion and employment status; autonomy and work area. The Pearson correlation indicated a weak correlation between the category of worker and the dimension of autonomy. In conclusion, the results indicate a favorable trend toward organizational climate.